Ultrasound and Nanomedicine for Cancer-Targeted Drug Delivery: Screening, Cellular Mechanisms and Therapeutic Opportunities - Chien-Hsiu Li; Yu-Chan Chang; Michael Hsiao; Ming-Hsien Chan (MDPI AG, 2022)
Cancer is a disease characterized by abnormal cell growth. According to a report published by the World Health Organization (WHO), cancer is the second leading cause of death globally, responsible for an estimated 9.6 million deaths in 2018. It should be noted that ultrasound is already widely used as a diagnostic procedure for detecting tumorigenesis. In addition, ultrasound energy can also be utilized effectively for treating cancer. By filling the interior of lipospheres with gas molecules, these particles can serve both as contrast agents for ultrasonic imaging and as delivery systems for drugs such as microbubbles and nanobubbles. Therefore, this review aims to describe the nanoparticle-assisted drug delivery system and how it can enhance image analysis and biomedicine. The formation characteristics of nanoparticles indicate that they will accumulate at the tumor site upon ultrasonic imaging, in accordance with their modification characteristics. As a result of changing the accumulation of materials, it is possible to examine the results by comparing images of other tumor cell lines. It is also possible to investigate ultrasound images for evidence of cellular effects. In combination with a precision ultrasound imaging system, drug-carrying lipospheres can precisely track tumor tissue and deliver drugs to tumor cells to enhance the ability of this nanocomposite to treat cancer.